"Machinery" or "spirit" of the welfare state: institutional change as institutional inertia. Issue 5 (13th June 2017) - Frericks, Patricia
Abstract : Purpose: Much has been said about institutional change and the forms it can take, whether it is abrupt or incremental, path breaking or path dependent. This strand of research is highly relevant in times of welfare institutional reforms and changes. A puzzle, however, remains, and it concerns the empirical phenomena that there might be institutional inertia despite seeming change. One reason for this remaining puzzle is, as argued here, that the ongoing theoretical reflections have a certain blind spot: "institutional constellations" and their characteristics. The purpose of this paper, therefore, is to analyse the "layering" of a welfare institution which results in an institutional constellation. Design/methodology/approach: Such newly established institutional constellations, though they look roughly similar and are formed of comparable ingredients, can differ profoundly between themselves. This could be due to the fact that the characteristics of institutions depend on the regulating principles (the "spirit") implemented in them. To validate this hypothesis, the author analyses in depth the institutional layering in two traditionally different social protection systems: the Dutch and the German pension systems. Findings: In both cases, as the author shows, the traditional regulating principles are also implemented in the newly established institutional constellation, so that in the end pension systems do not change but differ as they did before. Originality/value: The empirical phenomenon of institutional inertia despite seeming change has not yet been explicitly addressed. This is the case since the ongoing theoretical reflections have a certain blind spot: "institutional constellations" and their characteristics which are the focus of this paper.